The concept of corporate strategy (2009)
The Concept of Corporate Strategy. Por Kenneth R. Andrews. Homewood, III.: R. D. Irwin, 1980 Revised Ed. xi, 180 p.; 24 cm. Incluye referencias e índice. ISBN 0-256-02371-9.